Living Harmoniously In Diversity Exploring The Religious Harmony In Fiqh Ibadah Of Tengger Ethnic: A Case Study - Anggarini, Ida Fitri; Husni, Muhammad; Abdurrahman (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
Religious harmony is one of the most important issues in religious life. This research aimed to overview the religious harmony of Fiqh Ibadah in minority areas with the uniqueness of their religious life from the perspectives of Tengger Ethnic. Specifically, this qualitative case study aimed to explore the religious harmony of the Tengger Ethnic in Ngadas Village, Poncokusumo Malang which is well-known as one village with three traditions. The data were collected through semi-structured interviews, focus group discussions (FGD), and observation with five Tengger ethnic differential religious beliefs. We organized our analysis and discussion around their perspectives and the contexts in which the religious harmony in Fiqh Ibadah they encountered emerged. Six major themes emerged, which were (1) thaharah, (2) shalat, (3) tajhizul mayyit, (4) shaum; fasting, (5) zakat, and (6) hajj and umrah. Meanwhile, religious harmony in Ngadas Village fosters the feel of tasamuh, accepting the differences, and intercultural understanding that might be acceptable to be implemented in multicultural or plural country world wide.